Business system management and engineering from open issues to applications - Ardagna, Claudio A. (Lecture Notes in Computer Science, 2012)
The next generation of Business Process Management (BPM) methods and tools will support the development of a new generation of service-enabled applications that change and evolve over time. The trend is moving from relatively stable, organization-specific applications to dynamic ones supporting business processes. This book is an outcome of the International Workshop on Business System Management and Engineering (BSME 2010), held in Malaga, Spain, in June/July 2010, in conjunction with the TOOLS 2010 federated conferences and under the aegis of the EU Network of Excellence on Service Software and Systems (S-Cube). The goal of the workshop was to bring together experts in the fields of business process management, service-oriented architectures, and service security to discuss the current state of research and identify new issues, challenges, and research directions. The results of these discussions are reflected in this book.